Optimization of PID controller parameters using PSO for two area load frequency control - Brijesh Kumar Dubey; N. K. Singh; Sameer Bhambri (IAES International Journal of Robotics and Automation (IJRA), 2019)
In this paper, an evolutionary computing approach for determining the optimal values for the proportional-integral-derivative (PID) controller parameters of load frequency control (LFC) of two area power system is presented. The proposed approach employs a particle swarm optimization technique to find optimum parameters. The state space model of two area power system and an Eigen value based objective function is considered. The effectiveness of the proposed approach is compared with integral control. Simulation results justify the proposed approach in terms of damping the oscillations, improved settling time, less over/under shoots.